Proceedings of the Conference "Lithuanian MSc Research in Informatics and ICT" - Kurasova, Olga; Žilinskas, Julius; Dzemyda, Gintautas (Vilnius University Proceedings, 2019)
The conference "Lithuanian MSc Research in Informatics and ICT" is a venue to present research of Lithuanian MSc theses in informatics and ICT. The aim of the event is to raise skills of MSc students, familiarize themselves with the research of other students, encourage their interest in scientific activities. MSc students from Kaunas University of Technology, Vilnius University, and Vytautas Magnus University will give their presentations at the conference.
Keywords: Artificial Intelligence; Program Systems; Cyber Security; Optimization; Data Science